"Social Freedom" in the Twenty-First Century: Rereading Polanyi. Issue 4 (2nd October 2017) - Cangiani, Michele
Abstract: Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought — from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp — than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view — that is, to a radical approach to Polanyi's thought.